PERANCANGAN BIAYA PENDIDIKAN MENGGUNAKAN METODE ACTIVITY BASED COSTING (ABC) DI STIKES ‘XYZ’ - Haris Hidayat (INFOKOM (Informatika & Komputer), 2020)
This study aims to create a single tuition design using Activity Based Costing (ABC) based on business process in “XYZ” Higher Education Institute Of Health Science to find out the tuition fee per student per semester. This research was done STIKes “XYZ”, one of the health colleges in Bandung. The research method used in this research is using comparative descriptive method, which is comparing traditional tuition design with costing design using Activity Based Costing, then create a design to calculate the tuition cost using Activity Based Costing method. In the data collection is done by interview, observation and documentation. Calculation of tuition cost using Traditional Costing and Activity Based Costing method to get the result of tuition fee per student per semester as follows: 1) Tuition of Diploma III Program Nursing with traditional method is lower 1,21% than ABC method; 2) Tuition fee of Diploma III Midwifery with traditional method is higher 5,74% than ABC method; 3) Tuition of Undergraduate Program of Nursing with traditional method is lower 24,37% than ABC method; And 4) Tuition of Professional Ners with traditional method is 12,53% less than ABC method.